Multimedia security technologies for digital rights management - Zeng, Wenjun, 1967-; Yu, Hong Heather, 1967-; Lin, Ching-Yung (Academic Press, 2006)
Security is a major concern in an increasingly multimedia-defined universe where the Internet serves as an indispensable resource for information and entertainment. Digital Rights Management (DRM) is the technology by which network systems protect and provide access to critical and time-sensitive copyrighted material and/or personal information. This book equips savvy technology professionals and their aspiring collegiate protgs with the latest technologies, strategies and methodologies needed to successfully thwart off those who thrive on security holes and weaknesses. Filled with sample application scenarios and algorithms, this book provides an in-depth examination of present and future field technologies including encryption, authentication, copy control, tagging, tracing, conditional access and media identification. The authors present a diversified blend of theory and practice and focus on the constantly changing developments in multimedia applications thus providing an admirably comprehensive book. * Discusses state-of-the-art multimedia authentication and fingerprinting techniques * Presents several practical methodologies from industry, including broadcast encryption, digital media forensics and 3D mesh watermarking * Focuses on the need for security in multimedia applications found on computer networks, cell phones and emerging mobile computing devices.